Pathways from Neuroticism, Social Support, and Sleep Quality to Antenatal Depression during the Third Trimester of Pregnancy - Jiarui Chen (International Journal of Environmental Research and Public Health, 2022)
Background: Antenatal depression is a severe public health problem. Many studies support the concept that neuroticism, social support, and sleep quality are closely related to antenatal depression. However, there is little evidence concerning the influencing pathways of these variables on antenatal depression. The aim of this study is to investigate the pathways from neuroticism, social support, and sleep quality to antenatal depression during the third trimester of pregnancy. Methods: A cross-sectional study design was used. A total of 773 eligible women in the third trimester of pregnancy submitted valid questionnaires from June 2016 to April 2017. Instruments with good reliability and validity were used to measure neuroticism, social support, sleep quality, and antenatal depression. Structural equation modeling was used to explore the pathways from neuroticism, social support, and sleep quality to antenatal depression during the third trimester of pregnancy. Results: Antenatal depression is shown to be positively correlated with neuroticism and negatively correlated with social support and sleep quality. Neuroticism is shown to have a direct effect and indirect effects through social support and sleep quality on antenatal depression. Conclusions: Neuroticism influences antenatal depression directly and indirectly. Social support and sleep quality are the mediators of the indirect relationship between neuroticism and antenatal depression. Our results suggest that a personality test offered to all pregnant women could help detect a vulnerability to depression, whereupon intervention in the domains of sleep and social support could prove preventive.